Trade interdependencies in COVID-19-related essential medical goods: Role of trade facilitation and cooperation for the Asian economies - Sanchita Basu Das; Rahul Sen (Asian Development Bank (ADB), 2022)
This paper empirically investigates the state of trade interdependency for coronavirus disease (COVID-19) essential medical goods-vaccines and their value chains, personal protective equipment, and diagnostic test kits-across 29 Asia and the Pacific economies. Expanding on Hayakawa and Imai (2022), the analysis investigates whether trade facilitation, proxied by membership in regional trade agreements (RTAs), can help mitigate any adverse impact on trade in essential medical goods. The results confirm that while trade is critical for Asian economies, its nature differs. Low-income economies are largely dependent on imports, whereas selected middle- and high-income economies are part of two-way trade and engaged in low end of vaccine value chain. We find that onset of the pandemic had hurt exports of these goods. This adverse effect is found to be lowered for economies engaged in RTAs. This emphasizes role of governments in committing to RTAs and implementing trade facilitation measures.
Keywords: F12; F13; R11; 330; COVID-19; vaccine supply chain; essential medical goods; regional trade agreements